2006
DOI: 10.1524/ract.2006.94.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Direct labeling of isoniazid with technetium-99m for diagnosis of tuberculosis

Abstract: SummaryIsonicotinic acid hydrazide (isoniazid) is one of the most effective agents in tuberculosis therapy. Hence it was chosen as ligand for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Other studies in mice with i.v. administration show drug concentrations in the liver, lung and kidney that are several fold higher than the amounts estimated using PET imaging,34 while Roohi et al used a technetium-99m derivative of INH to determine the drug biodistribution in Sprague-Dawley rats giving similar drug concentrations in heart and lung but more than 10-fold higher concentrations in the liver and kidney compared to the other studies 35. Again, interspecies variation could play an important role in any differences observed between our study and those conducted in rodents, with the additional caveat that the study in rats involved the use of INH that had been modified with technetium-99m.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies in mice with i.v. administration show drug concentrations in the liver, lung and kidney that are several fold higher than the amounts estimated using PET imaging,34 while Roohi et al used a technetium-99m derivative of INH to determine the drug biodistribution in Sprague-Dawley rats giving similar drug concentrations in heart and lung but more than 10-fold higher concentrations in the liver and kidney compared to the other studies 35. Again, interspecies variation could play an important role in any differences observed between our study and those conducted in rodents, with the additional caveat that the study in rats involved the use of INH that had been modified with technetium-99m.…”
Section: Resultsmentioning
confidence: 99%
“…It was chosen as ligand for 99m Tc-labeling and imaging in the developed animal model with a gamma camera. The results suggested that 99m Tc-isoniazid was a specific agent for localization of tubercular lesions [66]. Kanamycin is an antibiotic used for treatment of infections when penicillin or other less toxic drugs cannot be used.…”
Section: Labelling Procedures and Kit Formulationsmentioning
confidence: 97%
“…177 Lu emits both beta (ÎČ) and gamma (Îł) particles; ÎČ‐particle emissions ( E max = 487, 383 and 175 keV) are used for remedy purpose of tumor and bone ache palliation, etc. and γ‐radiation (113 and 208 keV) for imaging …”
Section: Introductionmentioning
confidence: 99%